The role of rs2237781 within GRM8 in eating behavior. Issue 5 (23rd June 2013) - Gast, Marie‐Therese; Tönjes, Anke; Keller, Maria; Horstmann, Annette; Steinle, Nanette; Scholz, Markus; Müller, Ines; Villringer, Arno; Stumvoll, Michael; Kovacs, Peter; Böttcher, Yvonne
Abstract Introduction: The glutamate receptor, metabotropic 8 gene (GRM8) encodes a G‐protein‐coupled glutamate receptor and has been associated with smoking behavior and liability to alcoholism implying a role in addiction vulnerability. Data from animal studies suggest that GRM8 may be involved in the regulation of the neuropeptide Y and melanocortin pathways and might influence food intake and metabolism. This study aimed to investigate the effects of the genetic variant rs2237781 within GRM8 on human eating behavior. Methods: The initial analysis included 548 Sorbs from Germany who have been extensively phenotyped for metabolic traits and who completed the German version of the three‐factor eating questionnaire. In addition, we analyzed two independent sample sets comprising 293 subjects from another German cohort and 430 Old Order Amish individuals. Genetic associations with restraint, disinhibition, and hunger were assessed in an additive linear regression model. Results: Among the Sorbs the major G allele of rs2237781 was significantly associated with increased restraint scores in eating behavior (P = 1.9 × 10−4; β = +1.936). The German cohort and the Old Order Amish population revealed a trend in the same direction for restraint (P = 0.242; β = +0.874; P = 0.908; β = +0.096; respectively). A meta‐analysis resulted in a combined P = 3.1 × 10−3 (Z‐score 2.948). Conclusion: Our data suggest that rs2237781 within GRM8 may influence human eating behavior factors probably via pathways involved in addictive behavior.